2016
DOI: 10.1097/olq.0000000000000404
|View full text |Cite
|
Sign up to set email alerts
|

Gonococcal Conjunctivitis Despite Successful Treatment of Male Urethritis Syndrome

Abstract: We report a case of progressive, cephalosporin-susceptible, Neisseria gonorrhoeae conjunctivitis despite successful treatment of male urethritis syndrome. We hypothesize that conjunctival infection progressed due to insufficient penetration of cefixime and azithromycin and point out that extragenital infection and male urethritis may not be cured simultaneously in settings where the syndromic approach is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…8 Topical steroids and/or corneal surgery may also be used if corneal injury persists or progresses despite antibiotics. 9,10 Clinicians should consider gonococcal conjunctivitis in sexually-active adolescents with ocular symptoms and in adolescents presenting with urogenital STI. While the vast majority of conjunctival exposures become symptomatic, the incubation period from N. gonorrhea exposure to ocular symptoms varies from three to 19 days compared to two to seven days for urogenital gonorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…8 Topical steroids and/or corneal surgery may also be used if corneal injury persists or progresses despite antibiotics. 9,10 Clinicians should consider gonococcal conjunctivitis in sexually-active adolescents with ocular symptoms and in adolescents presenting with urogenital STI. While the vast majority of conjunctival exposures become symptomatic, the incubation period from N. gonorrhea exposure to ocular symptoms varies from three to 19 days compared to two to seven days for urogenital gonorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Ceftriaxone resistance is rare but has also been recorded. 11 It has been reported that insufficient penetration of some drugs such as cefixime and azithromycin in the conjunctiva may also result in the lack of a treatment effect. 3 Longer treatment times may help to achieve better effects, and the course depends on the recovery of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…GC in adults is generally thought to result from auto-inoculation of infected genital secretions through hand contact or contaminated towels from the patient or his/her partner. GC is often associated with STIs but can also present without evidence of concomitant genital infection, 2 or present despite successful treatment of urethritis syndrome. 3 GU and chlamydia are the most frequently reported STIs in developed countries, and concurrent treatment for chlamydia is now part of the recommended treatment regimen for GU 4,5.…”
Section: Introductionmentioning
confidence: 99%